Changes in climatic water balance drive downhill shifts in plant species' optimum elevations - Crimmins, Shawn M; Dobrowski, Solomon Z; Greenberg, Jonathan A; Abatzoglou, John T; Mynsberge, Alison R (Science (American Association for the Advancement of Science), 2011)
Uphill shifts of species' distributions in response to historical warming are well documented, which leads to widespread expectations of continued uphill shifts under future warming. Conversely, downhill shifts are often considered anomalous and unrelated to climate change. By comparing the altitudinal distributions of 64 plant species between the 1930s and the present day within California, we show that climate changes have resulted in a significant downward shift in species' optimum elevations. This downhill shift is counter to what would be expected given 20th-century warming but is readily explained by species' niche tracking of regional changes in climatic water balance rather than temperature. Similar downhill shifts can be expected to occur where future climate change scenarios project increases in water availability that outpace evaporative demand.